2017
DOI: 10.1111/ejh.12960
|View full text |Cite
|
Sign up to set email alerts
|

Successful collection of peripheral blood stem cells upon VIDE chemomobilization in sarcoma patients

Abstract: Our data demonstrate the feasibility of successful PBSC collection upon VIDE chemomobilization even after up to five cycles of induction therapy, while at the same time the increasing risk of bone marrow exhaustion with every consecutive cycle is outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Furthermore, in this reported cohort of 42 patients, two patients with insufficient mobilization received additional treatment with plerixafor. 5 The mobilization of the study's patients was performed with G-CSF alone, without addition of other mobilization factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in this reported cohort of 42 patients, two patients with insufficient mobilization received additional treatment with plerixafor. 5 The mobilization of the study's patients was performed with G-CSF alone, without addition of other mobilization factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in line with Kriegsmann et al, who reported about the mobilization data after first‐line treatment with VIDE in patients with soft tissue sarcoma in both pediatric and adult population (median age 28), showing the collections to be feasible even after the third course VIDE, but indicating the need for multiple leukapheresis sessions in later courses. Furthermore, in this reported cohort of 42 patients, two patients with insufficient mobilization received additional treatment with plerixafor 5 . The mobilization of the study's patients was performed with G‐CSF alone, without addition of other mobilization factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, all treatment options should be kept open for the individual patient, including HD-CHT and ABSCT in the case of relapse. To this end, PBSC collection should occur not too late in the treatment plan [30]. On the other hand, the cost for unused PBSC harvests over the years can easily add up to several million Euros in a large transplant center.…”
Section: Discussionmentioning
confidence: 99%